Parent-child Relations, Religiousness, and Adolescent Substance Use Disorders - Hoffmann, John P. (Journal of drug issues, 2023)
Research has shown that parent-child relationships and religiousness are negatively associated with substance use among adolescents, but few studies have addressed their relationship with substance use disorders (SUDs). This study explored whether high quality parent-child relations are negatively associated with the risk of an SUD among adolescents, especially when religiousness is high. The data used to assess this inquiry were from 4 years (2016–2019) of the U.S. National Survey on Drug Use and Health (NSDUH). SUDs in the past year were based on a set of questions consistent with criteria enumerated in the DSM-IV. Latent measures of parent-child relations and religiousness were also constructed. The results of an augmented inverse probability weighting (AIPW) model furnished empirical evidence in support of the notion that the lowest risk of an SUD occurred among those reporting high quality parent-child relations and high religiousness, even after adjusting for a substantial number of selection factors.